2019
DOI: 10.3390/polym11050918
|View full text |Cite
|
Sign up to set email alerts
|

Complex Permittivity and Microwave Absorption Properties of OPEFB Fiber–Polycaprolactone Composites Filled with Recycled Hematite (α-Fe2O3) Nanoparticles

Abstract: Recycled hematite (α-Fe2O3) nanoparticles with enhanced complex permittivity properties have been incorporated as a filler in a polycaprolactone (PCL) matrix reinforced with oil palm empty fruit bunch (OPEFB) fiber for microwave absorption applications. The complex permittivity values were improved by reducing the particle sizes to the nano scale via high-energy ball milling for 12 h. A total of 5–20 wt.% recycled α-Fe2O3/OPEFB/PCL nanocomposites were examined for their complex permittivity and microwave absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…The study of synthetic techniques for ferrite nanoparticles production has recently attracted considerable attention in view of their excellent magnetic and electrical properties [ 2 ]. Up to date, various techniques have been used for the synthesis of Fe 2 O 3 nanoparticles (Reference code: 00-024-0072) such as electrospinning technique [ 3 ], reduction-oxidation process [ 4 ], and hydrolysis process [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of synthetic techniques for ferrite nanoparticles production has recently attracted considerable attention in view of their excellent magnetic and electrical properties [ 2 ]. Up to date, various techniques have been used for the synthesis of Fe 2 O 3 nanoparticles (Reference code: 00-024-0072) such as electrospinning technique [ 3 ], reduction-oxidation process [ 4 ], and hydrolysis process [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The electro-Fenton system was synthesized by combining multiwall carbon nanotubes and Fe@Fe 2 O 3 nanowires with PTFE [ 19 ]. It is also worth noting that Fe 2 O 3 nanoparticles have been widely used as fillers to enhance the dielectric and magnetic properties of various matrixes such as polycaprolactone (PCL) [ 2 ], polyaniline (PANI) [ 20 ], silica [ 21 ], and poly(methyl methacrylate) (PMMA) [ 22 ]. However, rFe 2 O 3 nanoparticles have never been used as fillers in PTFE matrix for microwave absorption applications yet.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the 6–22 wt.% MWCNTs filler on the dielectric properties of OPEFB/PLA/MWCNTs composites was studied, and the variation in and values in the range of 8–12 GHz is shown in Figure 7 . It has been reported that the quality of conductive fillers distributed in a polymer matrix will play a significant role in the entire sample’s dielectric behaviors [ 26 ]. PLA polymer has low permittivity because of the small amount of macromolecular polarization.…”
Section: Resultsmentioning
confidence: 99%
“…The measurements for the complex permittivity of the composites were carried out using the OEC probe HP85071C technique (Agilent, Santa Clara, CA, USA). The probe was connected to an HP8720B Vector Network Analyzer (VNA) via a high-precision coaxial test cable [ 24 ]. The OEC probe is particularly suited for the measurements of complex permittivity of liquid.…”
Section: Methodsmentioning
confidence: 99%